2022
DOI: 10.1002/cbic.202200192
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Range of Acidity: Tracking Rules for the Unidirectional Penetration of Cellular Compartments

Abstract: Labeled ammonium cations with pK a ~7.4 accumulate in acidic organelles because they can be neutralized transiently to cross the membrane at cytosolic pH 7.2 but not at their internal pH < 5.5. Retention in early endosomes with less acidic internal pH was achieved recently using weaker acids of up to pK a 9.8. We report here that primary ammonium cations with higher pK a 10.6, label early endosomes more efficiently. This maximized early endosome tracking coincides with increasing labeling of Golgi networks wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 128 publications
(344 reference statements)
0
13
0
Order By: Relevance
“…Arguably the cleanest series of spectra was obtained for Flipper‐TR ® 1 at 13 n m ( Figure 5 ,A ). The response from the anionic but neutralizable [32] Flipper‐TR ® 1 was most convincing and consistent at all concentrations ( Figures 5 ,A , 5,D , S1 ). This result confirmed that detectable (planarizing) or undetectable (non‐planarizing) ion pairing of the cationic flippers 2 ( Figure 5, middle) and particularly the non‐neutralizable [32] 3 (right) with the non‐neutralizable [32] anionic phosphodiester backbone along DNA grooves was more disturbing than helpful.…”
Section: Figurementioning
confidence: 68%
See 4 more Smart Citations
“…Arguably the cleanest series of spectra was obtained for Flipper‐TR ® 1 at 13 n m ( Figure 5 ,A ). The response from the anionic but neutralizable [32] Flipper‐TR ® 1 was most convincing and consistent at all concentrations ( Figures 5 ,A , 5,D , S1 ). This result confirmed that detectable (planarizing) or undetectable (non‐planarizing) ion pairing of the cationic flippers 2 ( Figure 5, middle) and particularly the non‐neutralizable [32] 3 (right) with the non‐neutralizable [32] anionic phosphodiester backbone along DNA grooves was more disturbing than helpful.…”
Section: Figurementioning
confidence: 68%
“…The response from the anionic but neutralizable [32] Flipper‐TR ® 1 was most convincing and consistent at all concentrations ( Figures 5 ,A , 5,D , S1 ). This result confirmed that detectable (planarizing) or undetectable (non‐planarizing) ion pairing of the cationic flippers 2 ( Figure 5, middle) and particularly the non‐neutralizable [32] 3 (right) with the non‐neutralizable [32] anionic phosphodiester backbone along DNA grooves was more disturbing than helpful. Despite much precedence in the literature for cationic probes binding to DNA, [46,51] repulsion between negative charges is also understood as the basis of all DNA architectures.…”
Section: Figurementioning
confidence: 68%
See 3 more Smart Citations